If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(7 + m) = -125 (7 * -5 + m * -5) = -125 (-35 + -5m) = -125 Solving -35 + -5m = -125 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + -5m = -125 + 35 Combine like terms: -35 + 35 = 0 0 + -5m = -125 + 35 -5m = -125 + 35 Combine like terms: -125 + 35 = -90 -5m = -90 Divide each side by '-5'. m = 18 Simplifying m = 18
| 7-8v=3v-8 | | 4=6+x/3 | | 4+7(x-2x)=60 | | 2n-5n=-3 | | -4.9x+6.88x-1.25=0 | | -35-2r=-3r+4(2r-7) | | 21+8p=-2(4-p)-7 | | p-2/6=p-4 | | a+b-c=d | | 5h+2-(h)=22 | | 7=7-10x | | -4.9x+7.25x-1.25=0 | | 9+4y=2(3-1) | | 2.3+3n=0.8n+12 | | 2(x-4)+3x=4(x-5) | | 5.5-10=11 | | 106=2(-6b+5) | | =500(1.05)(9) | | 13=4p+5+4p | | 2x-27y+11xy=22 | | [x-5]=[x+2] | | 5=1-4a-8 | | 3x+y-8x+2y= | | 3(1-4x)+2(7x)=25 | | -8(4+9r)=7*(-2-11r) | | 18-5w+7w-4=28 | | 10-4h+2+5h=-12+9h | | 2(8n+9)=4(n+2) | | a-8+7=-6 | | 6y=8y-40 | | p-6/2=p-2 | | 2x-(4-x)=4[5-(4+9x-1)] |